2000
DOI: 10.1093/ndt/15.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dialysis therapy on insulin resistance in end-stage renal disease: comparison of haemodialysis and continuous ambulatory peritoneal dialysis

Abstract: CAPD therapy, in spite of its possible adverse effects in patients with atherosclerotic disease, has been shown to improve insulin resistance in adult uraemic patients, similarly to HD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 33 publications
2
59
2
2
Order By: Relevance
“…10,11 Its known that initiation of dialysis therapy partially revert those disturbances. 12 However, initiation of PD adds potential harm related to the great glucose absorption from PD fluids that lead to worsening of insulin resistance, dyslipidemia and higher levels of HbA1c. In the present study we confirm that the glucose and lipid metabolism profile in PD patients is worse than the observed in their HD counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Its known that initiation of dialysis therapy partially revert those disturbances. 12 However, initiation of PD adds potential harm related to the great glucose absorption from PD fluids that lead to worsening of insulin resistance, dyslipidemia and higher levels of HbA1c. In the present study we confirm that the glucose and lipid metabolism profile in PD patients is worse than the observed in their HD counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…After induction, peritoneal dialysis (PD) has been shown to initially improve insulin resistance in uremic patients, similar to hemodialysis (HD) (3). However, it is feared that with time the cumulative exposure to glucose solutions used in PD might lead to systemic hyperglycemia, obesity, and aggravate insulin resistance, which could contribute to increased cardiovascular risk (4).…”
Section: Introductionmentioning
confidence: 99%
“…Kobayashi et al showed that CAPD therapy with standard glucose containing solutions for 5.4 weeks normalized insulin resistance similar to hemodialysis therapy. [18] In contrast, Delarue reported that CAPD patients display an insulin resistance not explained by increased lipid oxidation. The maintenance of intracellular glucose utilization at the expense of higher glycemic and insulinemic responses suggests a defective glucose transport.…”
Section: Discussionmentioning
confidence: 98%